1997
DOI: 10.1007/s004360050240
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Trypanosoma congolense and T. brucei subspecies in cattle in Zambia by polymerase chain reaction from blood collected on a filter paper

Abstract: To facilitate epidemiology studies of African trypanosomiasis in cattle in Zambia, we adapted a polymerase chain reaction (PCR) method using blood spotted on filter papers. For easy preparation of template DNA from the dried blood, we adapted a simple DNA extraction method using Chelex-100, an anion-exchange resin. Using primers directed for repetitive nuclear DNA sequences, species-specific DNA amplifications were detected from the blood of rats infected with Zambian isolates of T. congolense and T. brucei su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 10 publications
1
16
0
Order By: Relevance
“…Indeed, MHCT, the standard parasitological method, presents a detectable limit of 500 flagellates/ml and the direct examination of wet or thin blood films requires at least 10 4 flagellates/ml to yield a positive result (Woo 1970). Considering that one single trypanosome has 100 fg of DNA, the used protocol showed to be extremely efficient in detecting parasitemias as low as 1 trypanosome/ml of blood (Penchenier et al 1996;Katakura et al 1997;Ijaz et al 1998). We observed that the blood spotted on filter paper confetti was useful and easy for T. evansi DNA detection, taking into account its feasibility under field conditions.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Indeed, MHCT, the standard parasitological method, presents a detectable limit of 500 flagellates/ml and the direct examination of wet or thin blood films requires at least 10 4 flagellates/ml to yield a positive result (Woo 1970). Considering that one single trypanosome has 100 fg of DNA, the used protocol showed to be extremely efficient in detecting parasitemias as low as 1 trypanosome/ml of blood (Penchenier et al 1996;Katakura et al 1997;Ijaz et al 1998). We observed that the blood spotted on filter paper confetti was useful and easy for T. evansi DNA detection, taking into account its feasibility under field conditions.…”
Section: Discussionmentioning
confidence: 93%
“…Polymerase chain reaction (PCR) has proved to be a very specific and sensitive tool, increasing the sensitivity of trypanosome detection, with great impact on the epidemiological studies, mainly in areas where cryptic infections occur (Katakura et al 1997;Davila et al 2003). Specific primers to PCR that amplify multicopy satellite regions were useful for Salivarian trypanosome detection in livestock, tsetse flies and humans (Moser et al 1989;Masiga et al 1992;Kanmogne et al 1996;Clausen et al 1998).…”
Section: Introductionmentioning
confidence: 97%
“…The reaction mixtures were overlaid with 20 µ paraffin oil (Sigma, UK) and cycled in a programmable heating block (Astek Inc. Japan) as follows: samples were incubated at 94°C for 3 min in an initial denaturing step and then were subjected to 40 cycles involving denaturation at 94°C for 1 min, annealing at 55°C for 1 min and extension at 72°C for 1 min. The samples were then incubated at 72°C for 7 min and then cooled to 4°C to stop the reaction 14 . Two µ of DNA loading buffer (Takara, Osaka, Japan) were added to the PCR product and 10 µ were placed onto a well of 2 % agarose gel in 1 × TAE buffer (40 mM Tris acetate, 1 mM EDTA).…”
mentioning
confidence: 99%
“…in a water bath before heating in boiling water for 8 min. The Chelex was removed by centrifugation at 10 000 rpm for 1 min and 100 µ of the supernatant fluid was transferred to a fresh centrifuge tube to serve as the sample template DNA for PCR amplification 14 . For each template sample, 3 separate 0.5 ml vials were prepared for T.congolense, T. brucei and T. vivax amplification.…”
mentioning
confidence: 99%
“…13) and is much higher than 18.7% (26/139) of the total tested rodents [13], though an infection rate up to 71% in field mice in Germany in early summer has been reported [6] and also in the United States [16]. The usefulness of the nested PCR technique in combination with the use of thin blood smears for detection of malaria and trypanosomasis has recently been reported [4,14]; however, method, which enable easy handling, transportation and storage of the test samples and is also very sensitive, may exclusively be very useful for remote and large-scale field surveys.…”
mentioning
confidence: 99%